OPTIMALISASI PENDISTRIBUSIAN ZAKAT MELALUI TRANSFORMASI PROSES BISNIS PERBANKAN SYARIAH SEBAGAI UPAYA PENGENTASAN KEMISKINAN DI SUMATERA UTARA - Ayu Annisa Fikra; Yenni Samri Juliati Nasution (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2024)
Zakat as one of the main pillars of Islamic economics has great potential in eradicating poverty, especially in North Sumatra, Indonesia, which has a fairly high poverty rate. However, the realization of zakat only reached 6.4% of the total national potential in 2023, indicating obstacles in distribution. This study aims to analyze the optimization of zakat distribution through the transformation of Islamic banking business processes as a poverty alleviation strategy. The research method used is qualitative with a literature study approach, which examines theories, concepts, and previous findings descriptively and analytically. The results of the study show that digital transformation, such as the integration of mustahik data and the digitization of payment systems, increases the efficiency of zakat distribution. In addition, the synergy between Islamic banks and zakat institutions (LAZ) creates a significant social impact, such as increasing mustahik income by up to 45%. The main obstacles identified include low digital literacy and limited technological infrastructure. Suggested solutions include digital literacy education, provision of technological infrastructure, and the use of blockchain technology to increase transparency and efficiency. This study provides practical implications for zakat managers, Islamic banking, and policy makers in supporting community empowerment through zakat as part of achieving the Sustainable Development Goals (SDGs).